Evaluation of isoprene emission rates of tropical trees by an iterative optimization procedure for G-93 parameters. (November 2018) - Higa, Takuya; Parveen, Shahanaz; Mutanda, Ishmael; Iqbal, Md Asif; Inafuku, Masashi; Hashimoto, Fumio; Oku, Hirosuke
Abstract: Isoprene emissions from six tropical trees were evaluated by "Ping-Pong" method that iteratively optimized the temperature ( C T ) and light ( C L ) parameters of the Guenther model, G-93. Six tropical trees; Bauhinia variegate (camel's foot tree), Calophyllum inophyllum (ball tree), Garcinia subelliptica (fukugi tree), Syzygium cumini (black plum), Syzygium samarangense (wax jambu), and Mangifera indica (mango; red and yellow fruit) were exposed to LED light in a phytotron. Saplings of Populus nigra were similarly treated under the same experimental conditions for reference. The irradiance protocol consisted of 26 steps and two cycles of increase and decrease in light intensity. Plants were exposed to a wide variation in light intensity (200–1500 μmol/m 2 /s), which resulted in leaf temperature variation of 29–40 °C. Predictions of isoprene emission by the optimized G-93 well captured the light and temperature dependent increase and decrease of isoprene emission rate in all tropical trees assessed. Comparatively, G-93 with default parameters showed lower efficacy in predicting emission rates during the ascending phase in the initial round, and at the peak phase in the second round of the irradiation scheme. G-93 with default parameters overestimated emissions at the initial ascending phase and underestimated at the second peak phase. Calculated Q10 values for isoprene emission from tropical trees were much higher than that of the temperate plant P. nigra under same observational conditions. These results strongly imply that isoprene emission behavior of tropical plants deviate from that of temperate plant. Highlights: We extended our previous study, and optimized the G-93 parameters for another six tropical trees by "Ping-Pong" method under laboratory conditions. Temperature responses of isoprene emission, Q10 between 30 and 40 °C, of all tropical trees predicted by optimized G-93 were greater than 5 contrasted with the Q10 values between 2 and 4 in the past studies for temperate plants. Increased observations on randomly selected tropical trees strengthened our proposal that G-93 parameters need revision to simulate regional isoprene emission from tropical areas.